Analysis of factors causing duplicate medical record numbers in the electronic medical record system at Hermina Opi Jakabaring Hospital Banyuasin Regency - Waskito, Hendri; Novratilova, Sinta (Institute of Computer Science (IOCS), 2025)
Along with the implementation of electronic medical records at Hermina Opi Jakabaring Hospital, various challenges have emerged in its implementation, one of which is the occurrence of duplicate medical record numbers. Duplication of medical record numbers is when a patient has two or more numbers in the medical record system. The purpose of this study was to determine the factors causing duplication of medical record numbers in electronic medical records. This research method is a descriptive qualitative method. Data were collected from 10 health workers through data collection with observation and interviews. Data were analyzed using the Fishbone method which includes five aspects, namely humans (man), equipment (machine), procedures (method), materials (material) budget (money), the results of the study showed that the biggest obstacle in the HR aspect was the lack of understanding and knowledge of officers about SOP, the unavailability of a medical card printing machine, SIMRS which does not yet have a NIK-based verification feature or a patient data duplication detection system, and the unavailability of a budget provided for the procurement of a medical card printing machine. This study provides strategic recommendations in overcoming duplication of medical record numbers so that it can improve the quality of service to patients.